2006
DOI: 10.1016/j.ygeno.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A human–horse comparative map based on equine BAC end sequences

Abstract: In an effort to increase the density of sequence-based markers for the horse genome we generated 9473 BAC end sequences (BESs) from the CHORI-241 BAC library with an average read length of 677 bp. BLASTN searches with the BESs revealed 4036 meaningful hits (E Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 18 publications
1
37
0
1
Order By: Relevance
“…whole genome sequence for the horse, projecting it to be ϳ 2700 Mb in size, i.e., ϳ 13% smaller than the human genome (size: ϳ 3100 Mb; Build 36.1). Similar observations were recently reported in horses (Leeb et al, 2006). Sequence data is presently available for the chimpanzee (PTR), dog (CFA), cattle (BTA), mouse (MMU), rat (RNO), opossum (MDO), and chicken (GGA) genomes and size estimates can be obtained for the region corresponding to the contig in these species.…”
Section: Comparative Size Of the Contig Across Speciessupporting
confidence: 81%
“…whole genome sequence for the horse, projecting it to be ϳ 2700 Mb in size, i.e., ϳ 13% smaller than the human genome (size: ϳ 3100 Mb; Build 36.1). Similar observations were recently reported in horses (Leeb et al, 2006). Sequence data is presently available for the chimpanzee (PTR), dog (CFA), cattle (BTA), mouse (MMU), rat (RNO), opossum (MDO), and chicken (GGA) genomes and size estimates can be obtained for the region corresponding to the contig in these species.…”
Section: Comparative Size Of the Contig Across Speciessupporting
confidence: 81%
“…Several single-gene disorders in quarter horses, such as polysaccharide storage myopathy (McCue et al, 2008;Tryon et al, 2009), hyperkalemic periodic paralysis, glycogen branching enzyme deficiency (Rudolph et al,1992), and hereditary equine regional dermal asthenia (Ward et al, 2004;Finno et al, 2009) has been reported due to wholegenome sequencing of an individual American quarter horse mare. A high-quality draft assembly was constructed and additional sequence were provided by the inclusion of bacterial artificial chromosome end sequences from a related male thorough bred horse (Leeb et al, 2006). Kinoshita et al, (2014) reported the genera Bacteroides and Prevotella especially B. fragilis and P. heparinolytica are dominant anaerobes in lower respiratory tract infection in horses.…”
Section: Sequence Analysis Studymentioning
confidence: 99%
“…The homologous human genome position of the end sequences for BAC '558', shown in FISH experiments to contain the distal breakpoint of the inversion, were determined by searching the database available at the Horse Genome Project web site (Leeb et al, 2006). Within these endpoints regions of high conservation approximately 3-5 kb apart were selected based on the conservation track of the UCSC Genome Browser (Kent, 2002).…”
Section: Primer Design For Breakpoint Screeningmentioning
confidence: 99%